2005
DOI: 10.1128/mcb.25.2.830-846.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rit Contributes to Nerve Growth Factor-Induced Neuronal Differentiation via Activation of B-Raf-Extracellular Signal-Regulated Kinase and p38 Mitogen-Activated Protein Kinase Cascades

Abstract: Rit is one of the original members of a novel Ras GTPase subfamily that uses distinct effector pathways to transform NIH 3T3 cells and induce pheochromocytoma cell (PC6) differentiation. In this study, we find that stimulation of PC6 cells by growth factors, including nerve growth factor (NGF), results in rapid and prolonged Rit activation. Ectopic expression of active Rit promotes PC6 neurite outgrowth that is morphologically distinct from that promoted by oncogenic Ras (evidenced by increased neurite branchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(171 citation statements)
references
References 80 publications
(150 reference statements)
13
153
5
Order By: Relevance
“…S6C). Notably, expression of RIT1 S35N , a presumptive dominant negative mutant analogous to RAS N17 (27), did not impair basal or EGF-induced ERK activation. These data suggest that RIT1 does not play a major role in normal RAS-ERK pathway activation, at least in Flp-In T-REx293 cells; i.e., the NS-associated mutants act as neomorphs.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…S6C). Notably, expression of RIT1 S35N , a presumptive dominant negative mutant analogous to RAS N17 (27), did not impair basal or EGF-induced ERK activation. These data suggest that RIT1 does not play a major role in normal RAS-ERK pathway activation, at least in Flp-In T-REx293 cells; i.e., the NS-associated mutants act as neomorphs.…”
Section: Significancementioning
confidence: 99%
“…RIT1 belongs to the RAS superfamily of small GTPases, and is >50% identical to RAS. Previous studies showed that an activated mutant of RIT1 (p.Q79L) can increase p38 MAPK and/or ERK activation in a cell-specific manner (27). The NS-associated mutations localize to the G2 domain (A57), G3 domain (A77), and switch II region (F82 and G95), which are conserved across vertebrates ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Ras GTPases respond to external signals by exchanging GTP for bound GDP, which enables interaction with downstream effector proteins, thereby linking extracellular signals to specific intracellular signaling cascades that mediate diverse cellular functions, including cell differentiation (Reuther and Der, 2000). We recently demonstrated that nerve growth factor (NGF) activates Rit and that Rit-GTP contributes to NGF-induced neurite growth in pheochromocytoma and SH-SY5Y cells (Spencer et al, 2002b;Hynds et al, 2003;Shi and Andres, 2005), suggesting that Rit signaling may be involved in controlling neuronal morphogenesis. The finding that Rit associates with the Par3-Par6 complex , which is involved in axon-dendrite specification in cultured hippocampal neurons (Shi et al, 2003), also supports a role for Rit in neuronal morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were transfected 72 h using Jetprime transfection reagent after the initial plating, which is necessary for HNPCs to regain contact. All DNA constructs used in this study have been described previously (27,28,54,55). Jetprime transfection reagent has been shown previously to mediate efficient transfection of murine neuronal stem cells (53).…”
Section: Methodsmentioning
confidence: 99%